2007
DOI: 10.1007/s10464-007-9133-0
|View full text |Cite
|
Sign up to set email alerts
|

Family Influences on Adolescent Delinquent Behaviors: Applying the Social Development Model to A Chinese Sample

Abstract: The current study applied the Social Development Model (SDM) to improve understanding of the mediation processes through which the family environment was related to Chinese adolescent delinquent behavior. We tested the hypothesized model using structural equation modeling with questionnaire data collected from 736 Chinese 7th and 9th graders, their parents, and their teachers from two middle schools in Beijing, China. Testing the model separately for boys and girls yielded adequate fit indices for both althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 50 publications
1
27
1
3
Order By: Relevance
“…Children living in families characterized by high levels of conflict, poor parental management and monitoring, and weak bonds among families members have been shown to be at increased risk for engaging in antisocial behavior and substance use (Deng and Roosa 2007; Kosterman et al 2004). The SDM hypothesizes that family social development processes are most salient during childhood and may lose some of this salience as children develop stronger bonds with peers and schools throughout adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Children living in families characterized by high levels of conflict, poor parental management and monitoring, and weak bonds among families members have been shown to be at increased risk for engaging in antisocial behavior and substance use (Deng and Roosa 2007; Kosterman et al 2004). The SDM hypothesizes that family social development processes are most salient during childhood and may lose some of this salience as children develop stronger bonds with peers and schools throughout adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative evidence of this isolation is found in a study of 32 Chinese immigrant adolescents; findings suggest that experiences of racist encounters alienated adolescents from both their peers and parents (Yeh, Kim, Pituc, & Atkins, 2008). Alienation and detachment from parents, in turn, has been linked to greater problem behaviors (Choi, He, & Harachi, 2008), more deviant beliefs (Deng & Roosa, 2007), and greater depressive symptoms (Ying, Lee, & Tsai, 2007) in both Asian American and Chinese adolescent samples. The influential nature of alienation from parents for Chinese samples in particular may stem from cultural values of filial piety and family obligation which are deeply rooted in Confucian values for Chinese families both in the U.S. and abroad (Chao & Tseng, 2002; Hsu, 1953; Qin, 2006).…”
Section: Effects Of Discrimination On Socioemotional Outcomesmentioning
confidence: 99%
“…They found that family attachment and parental supervision were significantly and negatively associated with substance use, but found no relationships between these family variables and deviant behavior. Deng and Roosa [8] also examined delinquent behavior with a number of family variables, including parental monitoring, family opportunities for conventional activities, adolescent involvement in family conventional activities, adolescent perceived parental rewards for desirable behaviors, and parental attachment. They analyzed data collected from 736 seventh and ninth graders, their parents, and their teachers from two middle schools in Beijing.…”
Section: Individual Group and Institutional Factors In Delinquency mentioning
confidence: 99%